PERANAN POS SAHABAT PEREMPUAN DAN ANAK DALAM MEMINIMALISIR KEKERASAN DALAM RUMAH TANGGA - Hengki Satrianta; Anna Rufaidah; Afiatin Nisa; Sabrina Dachmiati (Pusat Studi Gender dan Anak, IAIN Palu, 2022)
Domestic violence is a hotly discussed issue. Its coverage in the mass media is constantly conveyed to the public. From any point of view, the terms